PRE-SERVICE TEACHERS EXPERIENCES OF MENTORING RELATIONSHIPS DURING TEACHING PRACTICE - Lerato Hlengiwe Sokhulu (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
Mentorship is a global phenomenon where a skilled individual trains a less experienced individual. During teaching practice, pre-service teachers often learn the necessary skills and knowledge they can use when practicing as future teachers. This learning usually requires pre- service teachers (mentees) and in-service teachers (mentors) to establish good and professional relationships where there is support, learning and professional growth. The purpose of this study was to explore experiences of mentoring relationships that mentees form with their mentors during their teaching practice.  This study employed a qualitative approach within a case study methodology. Three undergraduate pre-service teachers were purposively selected to generate data on their mentoring experiences that allowed them to form specific relationships with their mentors. Semi-structured interviews were used to generate data from these participants. The data was analysed using thematic analysis in conjunction with the Cognitive Apprenticeship Theory (CAT). The findings of the study indicated that mentees were able to establish positive mentoring relationships with their mentors, which were influenced by many factors such as professionalism and prior interaction. However, in certain experiences, participants faced challenges establishing professional relationships with some of their mentors. Therefore, we concluded that the participants in this study can use what seemed to be negative relationship experiences as learning curves for their future teaching careers. Moreover, the study recommended that agency should be developed with mentees to be able to deal with both positive and negative mentoring relationships.